Activity-based therapy in the community for individuals living with spinal cord injury or disease: qualitative interviews with clinicians. Issue 17 (14th August 2022) - Cheung, Lovisa; Musselman, Kristin E.; Kaiser, Anita; Jervis Rademeyer, Hope; Walden, Kristen; Marshall, Sandi; Gauthier, Cindy
Abstract: Purpose: Activity-based therapy (ABT) is a restorative approach that promotes neurological recovery below the level of injury in individuals with spinal cord injury or disease (SCI/D). This study sought to understand how ABT and its associated technologies were being used in community-based facilities across Canada. Methods: One to two participants from ten community-based ABT facilities completed a semi-structured interview that queried types of technologies or techniques used in ABT, and barriers and facilitators to providing ABT for individuals with SCI/D. Interviews were audio-recorded and transcribed verbatim, and analyzed using an interpretive description approach to identify themes and categories. Results: The overarching theme that emerged was that ABT in the community is a client-centered approach characterized by variety in techniques, clinicians, and clientele. The researchers identified three categories within this theme: characteristics of ABT in the community, perceived challenges, and a need for advocacy. Participants advocated for earlier implementation, increased education, and reduced costs of ABT to address the challenges with implementation and accessibility. Conclusions: The use of ABT and its associated technologies varied across participating community-based facilities in Canada, despite a consistent focus on client goals and well-being. Addressing system-level limitations of ABT may improve implementation and accessibility in Canada. Implications for rehabilitation: Activity-based therapy (ABT) is a group of interventions targeting recovery of sensory and motor function below the level of injury in individuals with spinal cord injury or disease (SCI/D). ABT in the community emphasizes a client-centered approach and is characterized by variety in techniques, clinicians, and clientele. Participants advocated that earlier implementation, reduced costs, and increased education will help overcome barriers to providing ABT, ultimately assisting to facilitate neurorecovery in individuals with SCI/D. Challenges in implementation, accessibility, and knowledge of ABT exist, highlighting a need to explore and address system-level limitations in Canada.